2014
DOI: 10.1093/icesjms/fsu179
|View full text |Cite
|
Sign up to set email alerts
|

Exportation of excess feed from Mediterranean fish farms to local fisheries through different targeted fish species

Abstract: Coastal fisheries and sea cage aquaculture coexist along the coastal zone, and it has been suggested that wild fish feed on excess feed around farms. If this occurs, the condition of wild fish can increase and their lipid profile can become modified. However, the influence of fishfarming on coastal fisheries has not been described in detail. Four targeted species of different trophic gilds, Sardinella aurita, Caranx rhonchus, Mullus barbatus, and Pomatomus saltatrix were studied and the lipid profiles of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…Izquierdo‐Gomez et al . () examined four species of fish around Mediterranean fish farms and found total lipid content and fatty acid profiles from fish from up to around 10 km distant from farms to differ from those of fish caught further from farms. Effects are not limited to fish.…”
Section: Interactions Between Finfish Farms and Wild Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Izquierdo‐Gomez et al . () examined four species of fish around Mediterranean fish farms and found total lipid content and fatty acid profiles from fish from up to around 10 km distant from farms to differ from those of fish caught further from farms. Effects are not limited to fish.…”
Section: Interactions Between Finfish Farms and Wild Populationsmentioning
confidence: 99%
“…Likewise, Izquierdo‐Gomez et al . () found that fish caught directly around farm sites by small‐scale artisanal fishers had lipid signatures of fish that had fed on aquafeeds, whereas fish caught by trawl fisheries away from farms did not. Arechavala‐Lopez et al .…”
Section: Interactions Between Finfish Farms and Wild Populationsmentioning
confidence: 99%
“…; Izquierdo‐Gomez et al . ), although Ramirez et al . () noted that this signal may be confounded by other terrestrial signals such as sewage outfalls, which can also provide a food source for small carnivorous species.…”
Section: Synthesis and Discussionmentioning
confidence: 93%
“…For example, when sampling Atlantic cod and saithe adjacent to cages around Hitra and Øksfjord, Norway, Fernandez-Jover et al (2011b) found increased LA and OA, but decreased DHA and n-3:n-6 ratio in muscle and liver of both species (Table 2). When examining regional effects of aquaculture, Izquierdo-Gomez et al (2015) detected enhanced proportions of LA in market fish caught from artisanal fisheries, including round sardinella (Sardinella aurita), false scad (Caranx rhonchus), red mullet (Mullus barbatus) and bluefish (Pomatomus saltatrix), which may have been caught up to tens of kilometres from the nearest farm (Table 2). Across all study species and locations, there was a general trend for increasing C 18 FA (LA, OA and ALA) in the body tissues of wild fish feeding on aquaculture waste, suggesting these FA are the most useful FA biomarkers, where replacement of fish oils with terrestrial oils has occurred in aquafeeds.…”
Section: Vertebratesmentioning
confidence: 99%
“…In this way these wild fish play an important ecological role in reducing the particulated organic matter from the fish cages (= bioremediation process). As a consequence, fish farming affects coastal fisheries by increasing the wild fish biomass (Machias et al, 2004;Izquierdo-Gómez et al, 2014). In doing so, it may increase the spawning-stock biomass, amplify the larval recruitment (FernandezJover et al, 2009(FernandezJover et al, , 2015 and influence wild fish physiology (Uglem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%